In silico analysis and structure modelling of GaPH2, a conserved hypothetical proteins related to thermal stress response in glaciozyma antarctica PI12 - Makdi Masnoddin; Clemente Michael Wong Vui Ling; Nur Athirah Yusof (Universiti Malaysia Sabah, 2025)
The genomic data of the native Antarctic yeast, Glaciozyma antarctica PI12, has garnered attention due to its distinctive thermal adaptation. Nonetheless, a significant percentage of the proteins associated with thermal stress adaptation were identified as conserved hypothetical proteins (HPs), suggesting that these proteins have not yet been characterised through experimentation. Consequently, this research aims to determine the structural characteristics of GaHP2, a conserved HP previously shown to be involved in the thermal stress response. Functional annotation, physicochemical analysis, homology modelling and structure validation, and superimposition of models were employed to analyse the gene using computational tools such as NCBI BLAST, InterProScan, Expasy's ProtParam, Phyre2, AlphaFold2, ModRefiner, and UCSF Chimera. The results indicated that the homology modelling approach effectively generated reliable 3D models of GaHP2. On the basis of the high confidence score (PROCHECK), stereochemical quality (VERIFY3D), energy of the protein chain (ANOLEA), and RMSD of 0.540 Å, the proposed model was assessed as reliable. One interesting finding of the study was the correlation between the presence of aromatic clusters in GaHP2 and its stability at higher temperatures. The GaHP2 protein was also found to contain domains that encoded oxygen-binding and/or oxygen-transporting globins, as indicated by functional analysis. This suggests that these proteins were involved in the adaptation to the cold, where oxygen levels were relatively low. This research illustrates that thermal stress proteins may possess distinctive structural flexibility and stability that enable them to function under thermal stress, thereby safeguarding host organisms from heat aggregation and cold denaturation.